Hepatitis Viruses in Heamodialysis Patients: An Added Insult to Injury?. (6th March 2013) - Kosaraju, Kranthi; Faujdar, Sameer Singh; Singh, Aashima; Prabhu, Ravindra
Abstract : Hepatitis B (HBV) and hepatitis C (HCV) viruses are the most important causes of chronic liver disease in patients with end stage renal disease on hemodialysis. The prevalence of hepatitis infection among hemodialysis patients is high and varies between countries and between dialysis units within a single country. This case-control study was undertaken to estimate the occurrence of HBV and HCV infections in patients undergoing hemodialysis in our tertiary care center. All patients receving hemodialysis at our centre with HCV or HBV infection were included in the study. The total number of patients admitted for hemodialysis during the study period was 1710. Among these, 26 patients were positive for HBV, 19 were positive for HCV, and 2 were positive for both HCV and HBV. Mean age of the infected cases in our study was 48.63 years. Mean duration of dialysis for infected cases was 4.8 years while that of the noninfected controls was 3.18 years. The mean dialysis interval was twice a week. Interventions to reduce the occurrence of these infections are of utmost need to reduce the risk of long-term complications among hemodialysis patients.